The economics of risk and time - Gollier, Christian (MIT Press, 2001)
This book updates and advances the theory of expected utility as applied to risk analysis and financial decision making. Von Neumann and Morgenstern pioneered the use of expected utility theory in the 1940s, but most utility functions used in financial management are still relatively simplistic and assume a mean-variance world. Taking into account recent advances in the economics of risk and uncertainty, this book focuses on richer applications of expected utility in finance, macroeconomics, and environmental economics. The book covers these topics: expected utility theory and related concepts; the standard portfolio problem of choice under uncertainty involving two different assets; P the basic hyperplane separation theorem and log-supermodular functions as technical tools for solving various decision-making problems under uncertainty; s choice involving multiple risks; the Arrow-Debreu portfolio problem; consumption and saving; the equilibrium price of risk and time in an Arrow-Debreu economy; and dynamic models of decision making when a flow of information on future risks is expected over time. The book is appropriate for both students and professionals. Concepts are presented intuitively as well as formally, and the theory is balanced by empirical considerations. Each chapter concludes with a problem set.